Navigating Democratic Parenting Patterns in Parenting in the Digital Era - Helmi Helmi; Novina Anggreni; Sridila Sridila; Saputra Adiwijaya; Muhammad Zusanri Batubara; Osi Karina Saragih (West Science Interdisciplinary Studies, 2024)
The rapid advancement of technology and access to information in the digital age has greatly impacted children, known as the digital native generation. While technology offers easy access to information and educational tools, it also presents risks such as internet addiction and exposure to harmful content. The family, especially parents, plays a crucial role in shaping children's character. Parents need to teach, guide, and protect children from the negative impacts of technology. This article delves into the concept of democratic parenting, which is considered effective in addressing these challenges. In this approach, there is an emphasis on two-way communication, allowing both parents and children to express their opinions. It focuses on setting realistic boundaries, balanced supervision, and responsible development of digital skills. This parenting style helps children learn to manage their screen time and develop healthy digital habits. Additionally, children are taught to think critically, respect diverse opinions, and become independent. Parents should familiarize themselves with their children's technology, set time limits for using digital devices, choose safe and educational content, and actively engage in their children's digital activities. With the right guidance, children can utilize technology for positive self-development, tackle technological challenges, and grow into responsible, critical, and adaptable individuals.